Problematyka umów zapobiegających podwójnemu opodatkowaniu - Georgjew, Edward (Wydział Prawa i Administracji UAM, 1989)
Undertaking economic activity by natural and legal persons on territories of foreign countries brings about many legal and organizational problems, connected mostly with double taxation. Double taxation may appear in internal and international relations. It may be of economic or legal character. Preventing double taxation may consist in unilateral, partial or full, renouncement by the State of the rights to collect taxes, in concluding bilateral agreements with respect to double taxation, the agreements which to a considerable extent eliminate double taxation of economic and legal character, and in concluding multilateral agreements which have to take into account complicated diversification of tax systems of various countries. The first agreements to prevent double taxation were concluded in the 1920s and 1930 s. However, the majority of such agreements were concluded in the 1970s, on the basis of a model form of agreement to prevent double taxation worked out by the OECD. The agreements based on the above model are adequately modified according to the arrangement of mutual economic relations and the specificity of tax systems of respective countries. Nowadays the process of tax unification within regional economic systems may be observed. In particular, in the EEC countries the said process is known under the name of „tax harmonization". In the CMEA countries, a great diversity of tax constructions may be observed, despite similarities in socio-economic systems of those countries. It seems that the above diversity has been caused by the adoption of different formuli of managing the national economy in various countries. However, it may be supposed that irrespective of those formuli, an attempt to harmonize tax burdens between the CMEA countries will be undertaken in the future. The most efficient tool to meet the above aim seems to be international tax agreements through which the co-ordination harmonization or unification of tax systems of various countries might best be achieved.
The problems of agreements to prevent double taxation